Effects of residential proximity to industrial zone on respiratory symptoms among residents in Parit Raja, Batu Pahat - Isa, Khairul Nizam Mohd; Som, Nur Afza Natasha Md; Jalaludin, Juliana; Hashim, Nor Haslina (Universiti Putra Malaysia Press, 2024)
Introduction: The industrial park in the district of Parit Raja, Batu Pahat resulted in rapid growth of the town during the last 20 years and has been a reason of concern that this park also has contributed greatly to the problem of air pollution. The aim of this study was to evaluate the association between industrial air pollution and respiratory symptoms in adults living in the Parit Raja. Methods: A comparative cross-sectional study was undertaken among residents in the district of Parit Raja, Batu Pahat, Johor, Malaysia. A total of 110 residents aged between 19 and 65 years were randomly selected and information on personal characteristics and respiratory symptoms was obtained through a validated questionnaire. The prevalence of respiratory symptoms was compared between residents recruited from the areas situated about 5km radius of the industrial park (exposed) and >5km radius from the industrial park (comparative). Results: A total of 34.5 and 25.5 of adults from the exposed group reported experiencing coughing for the last 3 months and chest tightness for the last 3 years. The logistic regression models showed that symptoms of coughing was associated with the exposed group (aOR=6.34, 95 CI=2.08-19.35), male respondents (aOR=3.18, 95 CI=1.10-9.16) and who stay in Part Raja for more than 14 years (aOR=3.16, 95 CI=1.14-8.79). Conclusion: This study demonstrated that long-term air pollution exposures are consistently associated with respiratory symptoms in residents living in the proximity of industrial parks. Therefore, public health initiatives that aim to provide more conducive environment are needed, especially for residents living near industrial parks.